PERAN KELUARGA MUSLIM MELALUI PENDIDIKAN AGAMA DAN PENDIDIKAN SEKS USIA DINI SEBAGAI UPAYA IDENTIFIKASI DAN PENCEGAHAN PENYIMPANGAN SEKSUAL DI MASYARAKAT - Abdul Rahman Ramadhan; Nur Sari, Siti Aisyah (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
The phenomenon of sexual deviance is increasingly prevalent in society with increasingly diverse forms such as LGBT, Pedophilia, Masturbation, Exhibitionism, not a few of which even lead to adultery and rape. Many parents are indifferent to this phenomenon because they think that it only happens outside their family and think that their family will definitely be protected from sexual deviance. In fact, apart from traumatic factors, most sexual deviations in society are caused by parents's negligence in identifying and providing religious education and sexual education to their family members from an early age. The family as the smallest scope of life has a vital role in shaping the individual attitude, mentality and character. This research discusses the role of Moslem families in identifying and preventing sexual deviations through religious education and sexual education from an early age. This research is a library research, with content analysis and deductive analysis approaches as data analysis techniques. The purpose of this study is to provide an explanation of the important role of the Muslim family in the identification and prevention of sexual deviation, as well as examples of sexual education originating from Islamic teachings for children from an early age. The results of this study indicate that Muslim families through the roles of both parents have a major contribution in the identification and prevention of sexual deviations through early childhood sex education originating from Islam.